Ethical Review Of Information Technology Use In Electronic Medical Record Management At Welas Asih Regional General Hospital, West Java Province - Karina Wulan Safitri; Rizqy Dimas Monica; Matoeari Soelistijaningroem (International Journal of Health Engineering and Technology, 2025)
The rapid adoption of Electronic Medical Records (EMR) in healthcare presents ethical challenges related to data privacy and security. This study aimed to assess the application of ethical principles in EMR management at Welas Asih Regional General Hospital and identify the practical challenges faced by healthcare professionals. A qualitative approach was employed, utilizing data from questionnaires and observations. The sample consisted of 40 purposively selected healthcare staff. The findings revealed a high level of staff understanding and compliance with ethical protocols; 100% of respondents understood patient confidentiality, and 97.5% reported the existence of SOPs and audit trails. Despite this, a significant 60% of staff reported experiencing ethical dilemmas in their daily practice, highlighting a crucial gap between policy and real-world application. In conclusion, while the hospital's ethical framework for EMR is robust and well-understood, there is a need for continuous training and support mechanisms to address persistent ethical dilemmas. This is essential for maintaining patient trust and ensuring secure, responsible healthcare services.